Synergistic inhibition of colon cancer cell growth with nanoemulsion-loaded paclitaxel and PI3K/mTOR dual inhibitor BEZ235 through apoptosis - Zou H (Dove Medical Press, 2016)
Hong Zou,1,2 Li Li,1 Ines Garcia Carcedo,1 Zhi Ping Xu,1 Michael Monteiro,1 Wenyi Gu1 1Australian Institute for Bioengineering and Nanotechnology, The University of Queensland, St Lucia, Brisbane, QLD, Australia; 2Department of Pathology, Key Laboratory for Xinjiang Endemic and Ethnic Diseases, Shihezi University School of Medicine, Shihezhi University, Xinjiang, People’s Republic of China Abstract: Colon cancer is the third most common cancer in the world, with drug resistance and metastasis being the major challenges to effective treatments. To overcome this, combination therapy with different chemotherapeutics is a common practice. In this study, we demonstrated that paclitaxel (PTX) together with BEZ235 exhibited a synergetic inhibition effect on colon cancer cell growth. Furthermore, nanoemulsion (NE)-loaded PTX and BEZ235 were more effective than the free drug, and a combination treatment of both NE drugs increased the efficiency of the treatments. BEZ235 pretreatment before adding PTX sensitized the cancer cells further, suggesting a synergistic inhibition effect through the phosphatidylinositol-3-kinases/protein kinase B/mammalian target of rapamycin pathway. The 50% inhibitory concentrations for BEZ235 were 127.1 nM and 145.0 nM and for PTX 9.7 nM and 9.5 nM for HCT-116 and HT-29 cells, respectively. When loaded with NE the 50% inhibitory concentrations for BEZ235 decreased to 52.6 nM and 55.6 nM and for PTX to 1.9 nM and 2.3 nM for HCT-116 and HT-29 cells, respectively. Combination treatment with 10 nM NE-BEZ235 and 0.6 nM and 1.78 nM NE-PTX could kill 50% of HCT-116 and HT-29, respectively. The cell death caused by the treatment was through apoptotic cell death, which coincided with decreased expression of anti-apoptotic protein B-cell lymphoma 2. Our data indicate that the combination therapy of PTX with the phosphatidylinositol-3-kinases/protein kinase B/mammalian target of rapamycin dual inhibitor BEZ235 using NE delivery may hold promise for a more effective approach for colon cancer treatment. Keywords: combination therapy, signal pathway inhibitor, chemotherapy, nanomedicine